Dynamics of Entrepreneurial Ecosystem and Entrepreneurship Development: Evidence from Africa - Alhaji Abdulai; N. Raja Hussain (Cogent Business & Management, 2024)
This paper examines the dynamics of the entrepreneurship ecosystem and entrepreneurship development in Africa. This study is conceived on the premise that although enterprise-induced growth is documented to be the panacea for containing the rising unemployment, poverty rate, and worsening economic conditions, African enterprise-led policies have not generated the desired results with entrepreneurship development still slow. It is believed that the nature of entrepreneurial ecosystem might have contributed to poor entrepreneurship development, however, there is a paucity of evidence about this possible link. This paper is one of the foundational studies in the entrepreneurship literature that has applied quantitative analytical procedures to investigate how the dynamics of the entrepreneurial ecosystem influence entrepreneurship development in Africa. The paper operationalises the entrepreneurial ecosystem within the African context and investigates the short-run and long-run relationships between these proxies and entrepreneurship development in Africa. The paper employed the Autoregressive Distributed Lag (ARDL) to estimate the relationships and the Generalised Method of Moments (GMM) to validate the estimates. Annual data from 2000 to 2021 in 54 African countries were used for the study. This translated into 1184 observations in a 22-year data span. The paper revealed a positive consequence of the entrepreneurial ecosystem on entrepreneurship development in Africa in both the short-run and the long-run, however, the short-run estimates were not significant. It is concluded that the entrepreneurial ecosystem proxies: people (human capital), venture capital, infrastructure, system, and support are catalysts that drive entrepreneurship development in Africa in the long run. It is recommended that African enterprise-led policy should emphasise the entrepreneurial ecosystem that revolves around these constructs in order to develop an entrepreneurship culture and sustain the existing enterprises.
Keywords: 650; Autoregressive Distributed Lag (ARDL); capital; entrepreneurship development; entrepreneurship ecosystem; Generalised Method of Moments (GMM); infrastructure; people; system and support